2023
DOI: 10.1186/s12964-023-01058-8
|View full text |Cite
|
Sign up to set email alerts
|

When AHR signaling pathways meet viral infections

Abstract: Aryl hydrocarbon receptor (AHR) is a ligand-dependent transcriptional factor widely expressed among immune, epithelial, endothelial and stromal cells in barrier tissues. It can be activated by small molecules provided by pollutants, microorganisms, food, and metabolism. It has been demonstrated that AHR plays an important role in modulating the response to many microbial pathogens, and the abnormal expression of AHR signaling pathways may disrupt endocrine, cause immunotoxicity, and even lead to the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…In particular, AHR has been identified as a host dependency factor for a few enveloped viruses such as Dengue virus and Zika virus [ 53 ] – reviewed comprehensively in Hu et al . [ 54 ]. Moreover, Giovannoni et al have recently reported that AHR is transcriptionally upregulated upon SARS-CoV-2 infection both in vitro and in patients samples [ 37 ], speculating that SARS-CoV-2 requires AHR to evade cellular antiviral responses, as previously reported for flaviviruses [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, AHR has been identified as a host dependency factor for a few enveloped viruses such as Dengue virus and Zika virus [ 53 ] – reviewed comprehensively in Hu et al . [ 54 ]. Moreover, Giovannoni et al have recently reported that AHR is transcriptionally upregulated upon SARS-CoV-2 infection both in vitro and in patients samples [ 37 ], speculating that SARS-CoV-2 requires AHR to evade cellular antiviral responses, as previously reported for flaviviruses [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This transcription factor activates the expression of the mentioned proteins and also cytochromes P450 [ 43 ]. Besides regulating xenobiotics metabolism, Ahr has many functions and is considered a signaling protein [ 44 ]. There is also evidence that the interaction between Ahr and the antioxidant response element (ARE) via the nuclear factor E2-related factor 2 (Nrf2) can change the expression of antioxidant and xenobiotic metabolizing enzymes, including GST and NQO1 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, chlorpromazine exerts antiviral properties against SARS-CoV-2, the etiologic agent of the COVID-19 pandemic, and is currently in clinical trials (NCT04366739) for this viral infection [252]. Other viruses enter host cells via clathrin-dependent endocytosis (CDE) and are inhibited by several neuroleptics, including chlorpromazine, fluphenazine, perphenazine, prochlorperazine, and thioridazine, emphasizing an alternative, DA-independent mechanisms of action, likely mediated by AhR (functioning as an E3 ubiquitin ligase) [253][254][255].…”
Section: Antipsychotics As Antiviralsmentioning
confidence: 99%